2009
DOI: 10.1111/j.1399-0004.2009.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel PORCN mutations in focal dermal hypoplasia

Abstract: Focal dermal hypoplasia (FDH), Goltz or Goltz-Gorlin syndrome, is an X-linked dominant multisystem disorder characterized primarily by involvement of the skin, skeletal system and eyes. We screened for mutations in the PORCN gene in eight patients of Belgian and Finnish origin with firm clinical suspicion of FDH. First, we performed quantitative PCR (qPCR) analysis to define the copy number at this locus. Next, we sequenced the coding regions and flanking intronic sequences of the PORCN gene. Three de novo mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…Our diagnostic study detected this mutation in an additional 4 out of 53 unrelated probands. Combining previous studies and the current study, the c.1094G>A (p.R365Q) mutation was not detected in at least 680 control X chromosomes (Leoyklang et al, 2008;Bornholdt et al, 2009;Froyen et al, 2009;Maas et al, 2009). Interestingly, each of these nucleotides, c.178G and c.1094G, is part of a CpG dinucleotide and is therefore likely to represent a hotspot for PORCN gene mutations.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Our diagnostic study detected this mutation in an additional 4 out of 53 unrelated probands. Combining previous studies and the current study, the c.1094G>A (p.R365Q) mutation was not detected in at least 680 control X chromosomes (Leoyklang et al, 2008;Bornholdt et al, 2009;Froyen et al, 2009;Maas et al, 2009). Interestingly, each of these nucleotides, c.178G and c.1094G, is part of a CpG dinucleotide and is therefore likely to represent a hotspot for PORCN gene mutations.…”
Section: Discussioncontrasting
confidence: 55%
“…The p.G60R (c.178G>A) was reported previously as a mutation in one female patient (Wang et al, 2007) and was identified in three out of 53 unrelated female probands in our cohort. The c.1094G>A (p.R365Q) was identified previously as a mutation in four female patients (Leoyklang et al, 2008;Bornholdt et al, 2009;Froyen et al, 2009;Maas et al, 2009). Our diagnostic study detected this mutation in an additional 4 out of 53 unrelated probands.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 2007, mutations were reported in PORCN at Xp11.23 [Grzeschlik et al, 2007;Wang et al, 2007]. Over 100 different PORCN mutations have been reported [Lombardi et al, submitted for publication; Bornholdt et al, 2009;Clements et al, 2009;Froyen et al, 2009]. …”
Section: Discussionmentioning
confidence: 96%
“…19, 22 Froyen et al later identified PORCN variants and gene deletions in a cohort of patients with a clinical diagnosis of FDH. 23 FDH is characterized by phenotypic features, including longitudinal striation of the long bones, the combination of split hand with syndactyly and absence of rays (also termed 'lobster-claw hand'), as well as atrophy and linear pigmentation of the skin, herniation of fat through dermal defects and multiple papillomas of the mucous membranes or skin. Oral anomalies, in addition to lip papillomas, include hypoplastic teeth.…”
Section: Discussionmentioning
confidence: 99%